3PC-011 Hplc method development and validation to determinate resorcinol for quality control in pharmaceutical formulations - Ramos, J Cordero (Eur J Hosp Pharm, 2018)
BACKGROUND: The hidradenitis suppurativa (HS) is an inflammatory skin disease. Resorcinol is a phenol derivate, and in topical self-treatment decreases the size and pain of HS lesions. Topical 15% resorcinol is prepared as a pharmaceutical compound. In current literature, high performance liquid chromatography (HPLC) methods have been reported for determination of resorcinol, using different gradients of mobile phase mainly. PURPOSE: To assess the correct formulation, our objective is to develop an isocratic HPLC method for quality control. MATERIAL AND METHODS: To develop and validate the method, an Agilent 1260 HPLC system was used. Performed at 25°C, the separation was carried out in reverse phase column (Agilent Zorbax Eclipse XDB-C18 4.6 mm x 250 mm, 5 µm i. d.) (USA) with an isocratic mode. The mobile phase was methanol:water 40%:60%, the flow rate was 1 mL/minute and the injection volume was 10 mcL. A diode array detector was used (=280 nm). All reagents were analytical grade and bought from Sigma-Aldrich (USA). The calibration line was generated by least squares linear regression. The method accuracy (acceptance criterion of 99%–101%) and precision performed in a within-day and between-day anaylisis (five consecutive days) was assessed by five replicates run (low-, medium- and high-level concentration) and <1% variability as acceptance criterion. Spectral analysis 2D and 3D was performed to assess specificity and selectivity of method. RESULTS: There was an adequate separation under the chromatografic conditions presented. The retention time (mean ±SD) was 3.62±0.006 min. UV spectrum analysis demonstrated the specificity and selectivity of the method, since there were no co-eluates at the same retention time of resorcinol. The calibration line was y=8.6584x+11.8571(‘Y’:area under the curve and ‘X’:experimental concentration). It was linear (R2=0.99993). All the standards passed the acceptance criteria. The mean recovery percentage was 99.994% in all concentration levels. The coefficient of variation within-day was 0.082%, 0.042% and 0.128% for low-, medium- and high-point respectively, and between-day was 0.016%, 0.199% and 0.221% for low-, medium- and high-point respectively. CONCLUSION: The presented method shows a simplified way to analyse resorcinol by HPLC using UV detector. The performance of the method has been proven in terms of linearity, accuracy, precision, selectivity and specificity by a validation assay. REFERENCES AND/OR ACKNOWLEDGEMENTS: doi:10. 5740/jaoacint. 14–123 doi:10.1007/s40265-015-0516-5 doi:10.1111/j.1365–2230.2009.03 377.x doi:10.1155/2014/632591 No conflict of interest